An Infant with a Diagnostically Challenging Hepatic Teratoma, Hypofibrinogenemia, and Adrenal Neuroblastoma: Case Report. (May 2015) - Fried, Iris; Rom-Gross, Eitan; Finegold, Milton; Simanovsky, Natalia; Revel-Vilk, Shoshana; Ben-Neriah, Ziva; Weintraub, Michael; Pappo, Orit; Meir, Karen
Teratomas of the liver are exceedingly rare. Neuroblastoma is the most common, extracranial solid tumor of infancy. We describe the case of a 2-month-old, female infant who presented with an abdominal mass arising in the right lobe of the liver, and a severe coagulopathy, which necessitated cryoprecipitate infusion. Biopsy was interpreted as hepatoblastoma. Following resection, difficulty classifying the mass led to several consultations, and an eventual diagnosis of teratoma. During follow-up, the patient was diagnosed with right adrenal neuroblastoma, which, in retrospect, had been present before the hepatic resection. To our knowledge, these 2 tumors have never been reported together, or in combination with isolated hypofibrinogenemia.